2019
DOI: 10.24263/2304-974x-2019-8-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Features of the formation of taste sensations

Abstract: Introduction. An important characteristic that reflects the quality and forms the price of any food product is its organoleptic properties, for example, taste sensations arising from the use of the product. Currently, there is not enough data that reliably describes the mechanism of occurrence of taste sensations.Materials and Methods. The subject of research was carbohydrates, proteins, and sodium chloride. The phase structure was studied by x-ray diffraction. Diffraction curves were recorded on an HZG 4A X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Depending on structural organization of lamellae, starches are subdivided into the A-, B-, and C-types. The A-and B-types of amylopectin have identical conformation of the helix, while having different unit cells: the orthorhombic one for A-type amylopectin and hexagonal one for B-type amylopectin (Litvyak et al, 2019). Brief characteristics of the unit cells of starches are summarized in Table 1 (Sarko and Wu, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on structural organization of lamellae, starches are subdivided into the A-, B-, and C-types. The A-and B-types of amylopectin have identical conformation of the helix, while having different unit cells: the orthorhombic one for A-type amylopectin and hexagonal one for B-type amylopectin (Litvyak et al, 2019). Brief characteristics of the unit cells of starches are summarized in Table 1 (Sarko and Wu, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…One of the relevant problems related to food biotechnology is designing special food products or their components that have tailored properties and improved bioavailability to compensate for deficiencies of essential nutrients (Rastogi and Bhatia, 2019).Controlled variation in crystallinity allows one to obtain a more reactive product possessing improved mechanical properties, since the crystallinity index of native starches depends on their source and varies broadly from 15% to 45% (Rodrigues et al, 2020;Litvyak et al, 2019;Pozo et al, 2018;Bajer et al, 2013). We have previously shown that the efficiency of native starch amorphization depends (Purohit et al, 2019), tapioca (Singh et al, 2006), chickpea (Ghosal and Kaushal, 2019) Note.…”
Section: Introductionmentioning
confidence: 99%